Teaching practices in primary and secondary schools in Europe: insights from large-scale assessments in education. - Isac, Maria Magdalena; Araújo, Luísa; Dinis da Costa, Patrícia; Soto Calvo, Elena; Albergaria-Almeida, Patrícia; European Commission; Joint Research Centre (Publications Office, 2015)
This report offers a detailed description of teaching practices at the primary and secondary school levels and it explores some relationships between teaching practices and other factors such as student achievement and class size. The latest data from several large-scale assessments in education is used for these purposes, namely TIMSS & PIRLS 2011, PISA 2012 and TALIS 2013. The focus of the report is on the mapping of the frequency of different teaching practices across European Member States (EU MS) at ISCED levels 1 and 2 as measured in TIMSS/PIRLS at the fourth grade level, in PISA for 15-year olds and in TALIS for teachers in ISCED level 2.
OCLC: 931003791